Aprendizado não-cognitivo como resultado da escolaridade: um estudo comparativo da experiência do SENAI e de escolas acadêmicas convencionais - Costa, Darcy (1978)
The present study tries to find out the possibility of different Scholar organizations for promoting changes over uncognitive charactetistics from people of-low social class. fi comparison was established between groups of pupils -worker's children- attending apprenticeship junior courses of the National Industrial Apprenticeship Service (SENAI) and pupils with similar social and educational characteristics attending to academic schools in Rio de Janeiro City. The data obtained by Studying, showed that the SENAI kncw how to capitalize the experiences of the Industrial t;nterprise methodologicaly equiping itself for moulding the apprentice, according to the behaviour rules required by the labour world. 'l'he analyzed academic schools even though proclaming wider objetives like the autorealization of student, lacking of material and human infra-structure for that, get down the point of inciting in students an attitude of aversion to scüool. The quantitative results made evident higher seores in módernity for pU!lils of academic schools, while in authoritarism record, there wasn't meaning diferences between the groups.